Development of a functional fermented food (Dahi) - M.SUSMITA,; B.MADHURI,; K.S.L.RAMYA KRISHNA,; DR.M.SUDHAMANI, (International Journal of Pharma and Bio Sciences, 2017)
Functional foods are meant to deliver health through their consumption. The addition of therapeutic ingredients to foods can cause problems in their production and storage. In this study, Salvia hispanica (chia seeds) and Glycyrrhiza glabra (liquorice) were incorporated separately into Indian Yoghurt (Dahi). Salvia hispanica is a rich source of Omega fatty acids, lipids, phenolic compounds and natural oxidants. Glycyrrhiza glabra is used as artificial sweetener and herbal medicine. There was significant increase in acidity on storage in case of Dahi with Salvia hispanica but no increase in control or in Dahi with Glycyrrhiza glabra. Microbial count of the samples showed a general increase.